Perkembangan kesenian Dolalak tahun 1970-2021: Antara harapan dan tantangan zaman (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
This research is motivated by the author’s interest in further examining the influence of changes in the role of male dancers by female dancers that have a significant impact on the existence of Dolalak art in the present. The purpose of this research is to describe the condition of Dolalak art before the change in 1970, as well as to describe the role of artists and government in preserving Dolalak art. In conducting the research, the author used the historical method which consists of the stages of heuristics, criticism, interpretation, and historiography. Based on this research, the author managed to obtain several findings. First, Dolalak art has undergone many changes which are the result of creations and innovations from the artists as a form of effort to adjust to the challenges of the times. Second, the efforts made are not limited to the renewal of the performance concept only, but also include preservation efforts by making Dolalak art as a brand city of Purworejo Regency as well as part of the tourist village package.
Keywords: Culture; Dolalak